2018
DOI: 10.1002/adfm.201800592
|View full text |Cite
|
Sign up to set email alerts
|

Morphology‐Dependent Magnetism in Nanographene: Beyond Nanoribbons

Abstract: Imprinting self‐sustainable magnetic features into graphene has recently generated much interest owing to its potential application in spintronics. Several strategies for imprinting magnetic features into graphene are proposed theoretically. However, only a few of them are realized experimentally. Here, the first scalable synthesis of magnetic graphene nanoplatelets with diverse morphologies, including nanoribbons and triangular, pentagonal, hexagonal, and other polyhedral shapes, is reported. This material en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…60 A highly inhomogeneous fluorine coverage was found to produce multilayer islands, folds, wrinkles, and ripples, all containing a lower content of fluorine, consequently forming a conductive superstructure through which the charge transport, mediated by itinerant π-electrons, occurred preferentially. 60 61,62 (see Methods Section below for details) indicated that the ferromagnetically ordered state was stable up to temperatures exceeding 300 K, in good agreement with the experimentally derived TC. The electronic structure displayed as density of states (DOS) of the C18(OH)4F6 model provided insights into the magnetic exchange mechanism in the G(OH)F system (see Figure 4b).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…60 A highly inhomogeneous fluorine coverage was found to produce multilayer islands, folds, wrinkles, and ripples, all containing a lower content of fluorine, consequently forming a conductive superstructure through which the charge transport, mediated by itinerant π-electrons, occurred preferentially. 60 61,62 (see Methods Section below for details) indicated that the ferromagnetically ordered state was stable up to temperatures exceeding 300 K, in good agreement with the experimentally derived TC. The electronic structure displayed as density of states (DOS) of the C18(OH)4F6 model provided insights into the magnetic exchange mechanism in the G(OH)F system (see Figure 4b).…”
Section: Resultssupporting
confidence: 76%
“…The spontaneous formation of zigzag motifs during synthesis of G­(OH)F is supported by bond dissociation energies (BDEs) of fluorine atoms favoring defluorination along the motif (see Figure S26 in the Supporting Information). A transition temperature of 440 K estimated for C 18 (OH) 4 F 6 by using the Ising model on the honeycomb lattice , (see Methods section below for details) indicated that the ferromagnetically ordered state was stable up to temperatures exceeding 300 K, in good agreement with the experimentally derived T C . The electronic structure displayed as density of states (DOS) of the C 18 (OH) 4 F 6 model provided insights into the magnetic exchange mechanism in the G­(OH)F system (see Figure b).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations